Effect of Diabetes Mellitus Comorbidity on Mortality Risk in Tuberculosis Patients who Received Tuberculosis Treatment: A Meta-Analysis - Hakim Anasulfalah; Didik Gunawan Tamtomo; Bhisma Murti (Masters Program in Public Health, 2022)
Background: Tuberculosis or TB is a disease caused by the Mycobacterium tuberculosis complex. There are several comorbidities that experience severity and death when infected with tuberculosis or TB, namely hypertension, diabetes mellitus, cardiovascular disease, chronic kidney disease, cerebrovascular disease, and other diseases. This study aims to estimate the magnitude of the risk of death in Tuberculosis patients undergoing treatment with comorbid Diabetes Mellitus, with a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This was a systematic review and meta-analysis with the following PICO, population: Tuberculosis patients. Intervention: comorbidities of chronic diabetes mellitus. Comparison: without comorbid diabetes mellitus. Outcome: death. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles “Tuberclosis” OR TBC AND “Diabetes Mellitus” OR DM AND Mortality OR Death The included full-text articles are in English with a cohort study design from 2007 to 2021 and report the adjusted Odds Ratio (aOR) in a multivariate analysis. Article selection is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 12 cohort studies involving tuberculosis patients undergoing treatment from America, Europe, Africa and Asia were selected for a systematic review and meta-analysis. The data collected showed tuberculosis patients undergoing treatment with comorbid Diabetes Mellitus had a 1.68 times risk of death compared to COVID-19 patients without comorbid chronic kidney disease (aOR = 1.68; 95% CI = 1.42 to 1.99; p<0.001).Conclusion: Diabetes mellitus comorbidity increases the risk of death in tuberculosis patients undergoing treatment. Keywords: Diabetes Melitus, Tuberculosis, mortality Correspondence:Hakim Anasulfalah. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: isnanr28@gmail.com. Mobile: 081327215685.